Development of a Multiple Intelligences-Based Interest and Aptitude Instrument for Elementary School Students - Sitti Rahmah Marsidi; Grin Rayi Prihandini; Rully Afrita Harlianty; Ezik Firman Syah (About the Journal, 2026)
Interest and aptitude are essential aspects in developing students’ potential from an early age. Elementary school represents the initial phase for shaping children’s potential and character. However, the availability of valid and comprehensive instruments to identify students’ interests and aptitudes at an early stage remains limited. The development of students’ interests and aptitudes aligns with national education goals to optimize learners’ potential. Accurate identification enables educators and parents to direct students’ development in a more systematic manner as preparation for future education. This study aimed to examine the psychometric properties of the Interest Blank scale based on Multiple Intelligences theory in identifying elementary school students’ interests and aptitudes. A quantitative approach was employed through reliability analysis, item discrimination analysis, and construct validity using Exploratory Factor Analysis (EFA), followed by Confirmatory Factor Analysis (CFA). The participants consisted of 367 elementary school students in grades 4–6. The study involved 367 elementary school students in Grades 4–6, recruited using a non-probability sampling technique with a convenience sampling approach, in which the entire target population at the research site was included (total sampling). The results indicated that three dimensions met the reliability criterion (α > 0.70), while the remaining five dimensions were below the recommended threshold. Most items demonstrated adequate discrimination (r ≥ 0.30), although several items still require evaluation. Factor analysis showed that the data were suitable for analysis; however, the empirical structure did not fully replicate the eight-factor Multiple Intelligences model. Furthermore, the CFA results indicated that the proposed model did not achieve a satisfactory fit. These findings suggest that the Interest Blank scale has potential for further development through refinement of items and construct structure.Minat dan bakat merupakan aspek penting dalam pengembangan potensi siswa sejak usia dini. Jenjang Sekolah Dasar (SD) menjadi fase awal pembentukan potensi dan karakter anak. Namun, ketersediaan instrumen yang valid dan komprehensif untuk mengidentifikasi minat dan bakat siswa sejak dini masih terbatas. Pengembangan minat dan bakat sejalan dengan tujuan pendidikan nasional untuk mengoptimalkan potensi peserta didik. Identifikasi yang tepat memungkinkan pendidik dan orangtua mengarahkan pengembangan potensi secara lebih terencana sebagai bekal pendidikan selanjutnya. Penelitian ini bertujuan menguji kualitas psikometrik skala Interest Blank berbasis teori kecerdasan majemuk dalam mengidentifikasi minat dan bakat siswa. Pendekatan kuantitatif digunakan melalui analisis reliabilitas, daya beda aitem, dan validitas konstruk menggunakan Exploratory Factor Analysis (EFA) dan analisis lanjutan yaitu confirmatory factor analysis (CFA). Subjek penelitian berjumlah 367 siswa SD kelas 4–6 yang diperoleh melalui teknik non-probability sampling dengan pendekatan convenience sampling, serta melibatkan seluruh populasi sasaran (total sampling) di lokasi penelitian. Hasil menunjukkan tiga dimensi memenuhi kriteria reliabilitas (α > 0,70), sedangkan lima dimensi lainnya masih di bawah batas yang direkomendasikan. Sebagian besar aitem memiliki daya beda memadai (r ≥ 0,30), meskipun beberapa masih perlu evaluasi. Analisis faktor menunjukkan data layak dianalisis, tetapi struktur empiris belum sepenuhnya mereplikasi model delapan kecerdasan majemuk. Hasil uji CFA menunjukkan model yang diajukan belum fit. Temuan ini menunjukkan skala Interest Blank berpotensi dikembangkan lebih lanjut melalui penyempurnaan aitem dan struktur konstruk.